Parasitic communities of Hoplosternum littorale (Hancock, 1828) as indicators of environmental impact - Dias, Karina G. A. [UNESP]; Alves, Carlos A. [UNESP]; Da Silva, Reinaldo J. [UNESP]; Abdallah, Vanessa D.; De Azevedo, Rodney K. (Acad Brasileira De Ciencias, 2017)
The parasites are indicative of several biological aspects of their hosts, including their diet, migration, recruitment and phylogeny, but they can also be direct indicators of the environmental quality. Hoplosternum littorale is a fish that has a high commercial value in some South American countries. The fishes were collected from January to July 2012, in two locations of the Peixe River in the municipality of Anhembi, State of Sao Paulo, Brazil, which had different environmental and limnological characteristics (river mouth and Lagoa Cabeca de Boi). An amount of 30 fish specimens were captured in each location for the analysis of their parasitic fauna. Nine species of metazoan parasites were collected. Both Brillouin's diversity index and Margalef's richness index were greater in the Lagoa Cabeca de Boi. The ratio of heteroxenous and monoxenous parasite species richness (S-H/S-M) was higher in the Lagoa Cabeca de Boi. The results of the physicochemical analysis of the water showed that the mouth of the Peixe River can be considered an area that suffers more from anthropogenic actions than the Lagoa da Cabeca de Boi. Proteocephalus sp., Gyrodactylus sp., Scleroductus sp. and Capillaria (Neocapillaria) pterophylli are being registered for the first time in this host.
Keywords: bioindicators; Callichthyidae; parasites; Peixe River; Sao Paulo